Treatment of a Gustilo-Anderson type II open tibia shaft fracture with an ultrathin silver plasma-coated plate: A case report. (December 2022) - Alt, Volker; Pfeifer, Christian; Rupp, Markus; Walter, Nike
Abstract: The treatment of open tibia fractures with plate fixation bears a high risk for the development of a fracture-related infection. Here we present a case of an 80-year-old female with a Gustilo-Anderson type II open distal tibial shaft fracture with an indwelling knee prosthesis. The case was successfully treated with a 2-stage procedure with initial external fixation and subsequent open reduction and plate fixation with a custom-made ultrathin silver plasma-coated locking plate. Plate fixation was the preferred method as the indwelling knee prosthesis prevented the use of a standard intramedullary tibia nail. The fracture healed uneventfully without any signs of infections and the patient achieved full weight-bearing with a normal gait and without any pain after three months. Radiographical full bridging of the initial fracture area was seen after 5 months without any signs of infection or fracture healing disturbances. After an overall follow-up of 12 months, there were no signs of silver associated or other adverse events. Thus, ultrathin silver plasma coating seems to be helpful in the treatment open fractures with plate fixation to prevent fracture-related infections.